2010
DOI: 10.1152/ajpendo.00608.2009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic functions of atypical protein kinase C: “good” and “bad” as defined by nutritional status

Abstract: tein kinase C (aPKC) isoforms mediate insulin effects on glucose transport in muscle and adipose tissues and lipid synthesis in liver and support other metabolic processes, expression of enzymes needed for islet insulin secretion and hepatic glucose production/release, CNS appetite suppression, and inflammatory responses. In muscle, selective aPKC deficiency impairs glucose uptake and produces insulin resistance and hyperinsulinemia, which, by activating hepatic aPKC, provokes inordinate increases in lipid syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 62 publications
1
81
1
4
Order By: Relevance
“…However, notwithstanding this difference in aPKC isoform expression, our studies reveal that a substantial depletion of PKC results in enhanced insulin sensitivity as judged using PKB activation and insulin-stimulated glucose uptake as readouts. This finding runs counter to the suggestion [see review and references cited therein (14)] that aPKCs are indispensible components of the mechanism underpinning the insulindependent stimulation of glucose uptake, at least in the cell model used in the current studies. In contrast, the observed increase in insulin sensitivity of PKC-depleted cells is consistent with the view that aPKCs may normally function to restrain IRS-1 and PKB-directed signaling.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, notwithstanding this difference in aPKC isoform expression, our studies reveal that a substantial depletion of PKC results in enhanced insulin sensitivity as judged using PKB activation and insulin-stimulated glucose uptake as readouts. This finding runs counter to the suggestion [see review and references cited therein (14)] that aPKCs are indispensible components of the mechanism underpinning the insulindependent stimulation of glucose uptake, at least in the cell model used in the current studies. In contrast, the observed increase in insulin sensitivity of PKC-depleted cells is consistent with the view that aPKCs may normally function to restrain IRS-1 and PKB-directed signaling.…”
Section: Discussioncontrasting
confidence: 99%
“…14 for a review). Based on expression of dominant interfering aPKC isoforms and use of nonselective PKC inhibitors, it has been suggested that activation of aPKCs in response to insulin is essential for promoting GLUT4 translocation to the cell surface and for supporting the associated increase in glucose uptake (14). However, somewhat paradoxically, activation of aPKCs by proinflammatory stimuli such as tumor necrosis factor-␣ (24), saturated fatty acids, and fatty acid-derived lipids such as ceramide (8,29) is associated with marked suppression of both insulin signaling and glucose transport (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical protein kinase C (aPKC) isoforms mediate insulin effects on glucose transport in muscle and adipose tissues and lipid synthesis in liver and support other metabolic processes ( 41 ). Hepatic aPKC-dependent activation of sterol regulatory binding protein-1c and nuclear factor-B contributes to the development of hepatic lipogenesis, hyperlipidemia, and systemic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Frøsig et al (35) reported that acute one-legged exercise by men did not alter subsequent (4 h postexercise) insulinstimulated atypical PKC (aPKC) activity without exogenous phosphatidylinositol-3,4,5-trisphosphate (PIP3), but aPKC activity measured with exogenous PIP3 was greater for the exercised vs. unexercised leg. Conflicting results implicate aPKC as being positively related, negatively related, or unrelated to insulin-stimulated glucose uptake (28,29,109,120). Frøsig et al (35) also reported greater IRS-2/PI3K for the exercised vs. unexercised leg, but IRS-1 appears to be more important than IRS-2 for insulin-stimulated muscle glucose uptake (7,53,115).…”
Section: Potential Mediatorsmentioning
confidence: 99%